INFLUENCIA DEL CULTIVO DE LUPINUS LUTEUS L. EN LA DENSIDAD DE INÓCULO DE PHYTOPHTHORA CINNAMOMI EN SUELOS DE DEHESA - Serrano, M. S.; Sanchez, M. E.; De Vita, P.; CARBONERO, M. D.; Trapero, A.; FERNÁNDEZ-REBOLLO, P. (Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas, 2009)
Phytophthora cinnamomi is a pathogen causing root rot in oak trees growing in dehesa sys- tems and also in yellow lupine, a common pasture crop in western Andalusia. In dehesas show- ing different situations in terms of tree decline and disease severity in the lupines, isolation and counting of colonies of P. cinnamomi from soil samples has shown the ability of the herbaceous crop to maintain or increase the inoculum density and thus may enhance oak infections. The obtained results discourage the cultivation of this legume in dehesas with known presence of the pathogen in the soil, whether the trees are suffering the root disease or not.
The following values have no corresponding Zotero field: periodical: Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas pub-location: Huesca
Keywords: decline; Holm oak; root rot; yellow lupine

Pathogenicity of Pythium spiculum and P-sterilum on feeder roots of Quercus rotundifolia - Jimenez, J. J.; Sanchez, J. E.; Romero, M. A.; Belbahri, L.; Trapero, A.; Lefort, F.; Sanchez, M. E. (PLANT PATHOLOGY, 2008)
APSAPSThe following values have no corresponding Zotero field: pub-location: 9600 GARSINGTON RD, OXFORD OX4 2DQ, OXON, ENGLAND publisher: BLACKWELL PUBLISHING
Keywords: pathogenic; Pythium spiculum; Pythium sterilum; Quercus ilex

Pathogenicity of three Phytophthora spp. causing late seedling rot of Quercus ilex ssp. ballota - Sanchez, M. E.; Andicoberry, S.; Trapero, A. (Forest Pathology, 2005)
Within a research project on quality of plants for forestation of agricultural lands, we studied the aetiology of a late seedling rot affecting holm oak (Quercus ilex ssp. ballota) in two forest nurseries in southern Spain. Major disease symptoms were foliage wilting and necrosis of feeder roots. Phytophthora cinnamomi, Phytophthora cryptogea and Phytophthora drechsleri were isolated from necrotic roots of holm oaks. Selected isolates of the three Phytophthora species were pathogenic to Quercus ilex ssp. ballota and Quercus suber seedlings in artificial inoculations. Soil flooding conditions were essential for infection and root rot development. There was no host specificity among the species, the isolates of P. cinnamomi being the most virulent in all inoculated plants. In these inoculations, Q. ilex ssp. ballota plants were more susceptible than those of Q. suber. This work is the first report of P. cinnamomi, P. drechsleri and P. cryptogea affecting Q. ilex ssp. ballota in forest nurseries.
The following values have no corresponding Zotero field: publisher: Blackwell Verlag GmbH
Keywords: Holm oak; Nurseries (voyant); Phytophthora spp.; root rot; Soil water content

Etiología de las podredumbres radicales de plántulas de QUERCUS SPP. Y PINUS HALEPENSIS EN VIVEROS FORESTALES DE ANDALUCÍA - Andicoberry, S.; LORA, F.; SÁNCHEZ, E.; Trapero, A. (III Congreso Forestal Español, 2001)
A disease surey carried out during 1998-99 showed that holm oak (Quercus ilex) and Aleppo pine (Pinus halepensis) seedlings were affected by damping-off and root rot in three forest nurseries in Andalucía, southern Spain. A similar problem was detected affecting four species of Quercus (Q. coccinea, Q. faginea, Q. ilex, and Q. suber) in a forest nursery in 2000. Three species of Phytophthora (P. cinnamomi, P. cryptogea, and P. drechsleri) were isolated from holm oak feeder roots, and P. drechsleri was isolated from feeder roots of Aleppo pine in the first survey in 1998-99. In the second survey, Cylindrocarpon didymum was isolated from the feeder roots of the four Quercus spp. essayed, and C. destructans was isolated only from Q. faginea. Pathogenicity tests were conducted using 1 year-old healthy plants of cork oak, holm oak and Aleppo pine. Isolates of the three Phytophthora species were pathogenic to the three host species, inducing root rot and plant death. Holm oak was the most susceptible host and P. cinnamomi was the most virulent species. Isolates of Cylindrocarpon were pathogenic to cork oak and holm oak causing root rot, yellowing, defoliation, and plant death.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español pub-location: Granada
Keywords: Cylindrocarpon; Phytophthora; Quercus coccinea; Quercus faginea; Quercus ilex; Quercus suber